Management strategies of mothers of school-age children with autism: Implications for practice - Joosten, Annette; Safe, Annaleise (Wiley-Blackwell Publishing Asia, 2014)
Background/aim: Mothering children with autism results in mothers spending more time on daily tasks as well as managing the disorder. The need for mothers to self-manage often increases when the child is school aged. Mothers develop strategies, and occupational therapists and other health professional rely on or expect mothers to be involved in meeting the extra needs of their children with autism and other family members. Little is known about the strategies adopted by the mothers. The aim of this study was to explore the strategies mothers used to manage their roles and emotions, and their child's behaviours.Method: In-depth individual interviews were conducted with seven mothers and data were analysed in this qualitative study using phenomenological analysis.Results: Findings revealed that the mothers had adopted strategies to manage their roles, their emotions and their child's behaviour. However, the strategies were often shaped by the expectations of others or circumstances beyond their control and at times added further to their stress.Conclusions: Mothers of children with autism developed strategies to self-manage their lives and their child's disorder. However, even when these strategies were effective, they sometimes placed further stress on the mothers. The mothers provided insights to how they coped but need help to consider the support they require and therapists need to consider the pressures of expecting mothers to self-manage their child's disorder, their own lives and their family. Family-centred practice emphasising collaboration with mothers needs to be maintained with school-aged children.